A Philosophical Jester: Thoughts and Jokes in Stoppard’s Arcadia and its Preliminaries - P. Müller, Péter (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Although the epoch of great narratives is said to be over, and encyclopaedic knowledge of the sciences and the humanities is impossible, playwright Tom Stoppard seems to represent a unique example of thorough intellectual knowledge in his works. Thoughts and theories are permanent and outstanding components of his plays. In 19th century critical realist fiction all sorts of information served as part of the social panorama and represented the dominance of the omnipotent narrator. In the 20th century the polyhistoric novel (Broch’s term) fulfilled a similar function with its complicated structure, polyphonic narrative and polymath author. In Stoppard’s plays the borrowed, referred and cited ideas have several simultaneous functions. Stoppard does not pretend to be the inventor of these thoughts even if he does not identify his sources. Theories function as demonstration of the relativity of the characters’ experience. They countervail both emotions and thoughts. Theories are often parodied and indirectly criticised by being staged. Theoretical discourse appears as part of the literary discourse, and although the arguments do not lose their textual features, their function becomes different; namely, they take on the polyphonic openness of literature. Stoppard’s thoughts and theories are intellectual games, comic parodies, and theatrical inventions at the same time. Borrowing plots, characters, structures, genres, and different theoretical views, Stoppard creates a special quality of dramatic art in which theory is a particular, essential component.